Estudo da transição cristalográfica em filme fino de VO2 por difração de raios-x - Escobar, Vivian Montardo (2011)
In one sample, X-Ray diffractions have been measured as a function of the temperature, in order to follow the crystallographic transition experienced by VO2 near 68ºC. The results have been analysed with the aide of a software based in the Rietveld structure refinement method. Below the critical temperature, the material is in a monoclinic M1 phase, with the V-V dimers parallel to the substrate. Near transition temperature, is has been identified a coexistence of the M1 and R phases, separated by a M2 region. The coexistence occurs inside individual grains. In contrast with the M1 and R phases, frequently identified in the VO2 transition, this is the first time the M2 phase is reported in < 011 > textured polycrystalline films of VO2 deposited by magnetron sputtering. A comparison between the M1 and R peaks width, at room temperature and (95ºC) respectively, shows the M1 phase is under inhomogeneous stress. Although in average those stresses are tensile, an important fraction of the sample is under compressive stress, what could explain the presence of the M2 phase.